The efficacy and safety of niraparib for ovarian cancer: a single-center observational study from China - Jing Ni; Xianzhong Cheng; Qian Zhao; Zhiqin Dai; Xia Xu; Wenwen Guo; Hongyuan Gu; Rui Zhou; Yan Wang; Xiaoxiang Chen (BMC, 2021)
Abstract Background Niraparib, a poly (ADP-ribose) polymerase (PARP) inhibitor, is approved for first/second-line maintenance treatment of ovarian cancer patients with complete or partial response to platinum-based chemotherapy, and multi-line monotherapy in BRCAmt patients or platinum-sensitive recurrence patients with homologous recombination deficiency (HRD). We present real-world experience from a single center of China. Methods Patients treated with niraparib in Jiangsu Cancer Hospital between June 2019 to July 2020 were recruited. The initial dose was given according to individualization. Response and adverse events (AEs) were analyzed by Response Evaluation Criteria in Solid Tumors v1.1. and National Cancer Institute Common Terminology Criteria for Adverse Events v5.0, respectively. HRD testing (AmoyDx®) was detected in most patients. Treatment was given until unequivocal progression or intolerable toxicity. Results Twenty-two patients all received niraparib at a bolus of 200 mg/d. Fifty percent of patients with high-grade serous ovarian cancer are HRD-positive. Six patients underwent first-line maintenance therapy. Sixteen patients received exploratory therapy. Ultimately image evaluation revealed that two patients achieved partial response (PR) and one patient achieved stable disease (SD), yielding objective response rate (ORR) of 33.3% (95%CI = 0.060-0.759) and disease control rate (DCR) of 50% (95%CI = 0.140-0.861) in the exploratory multi-line monotherapy group. The most common AEs were nausea, thrombocytopenia, and anemia. Grade 3-4 thrombocytopenia were managed by dose reduction and interruption. Leg swelling was observed as a new adverse event. Conclusion It is feasible that patients receiving a bolus of 200 mg/d in patients from Chinese population can acquire promising efficacy and tolerance. This is the first real-world data about niraparib in ovarian cancer patients with available HRD status from China.